The Existence of Makka Keke’s Belief System in Gantarang, Selayar - Hasaruddin Hasaruddin; Misbahuddin Misbahuddin (Universitas Islam Negeri Alauddin Makassar, 2016)
The impurity of Islam understood by most Indonesian Muslims at the beginning of dissemination constitutes to a form of adaptation through assimilation between Islam and local tradition that animism and dynamism are found, so that the Indonesian Muslims show things that are contrary with principles of Islam, especially those are related to the principles of Islamic’s theology that rejects all forms of musyrik and khurafat. The sinkretisme happens and experiences over all archipelago in general and continues to be-so, at least before some Islamic reform movement is present as neutralizing the situation. The existences of Islamic reform movements are not able to eliminate the ongoing process of acculturation. There is no much efforts provided considering that all movements in colonial period are limited. It is only at the time of Indonesia's independence that is all movements by reformist and traditional ulama are in move to act the upheaval including those take place in Selayar with Makka Keke’s belief system in the village of Gantarang.